A construção de ideias no processo de projeto de arquitetura - Isabel Campos Caldeira Brant (2019)
This dissertation investigates ideation in the design process in Architecture, aiming to identify the intervening factors in the development of ideas, assuming that a better comprehension could contribute to the improvement of design practice and education. Instrumentation was approached with the objective of comprehending its repercussions in the construction of architectural ideas. An emphasys was given to Building Information Modeling (BIM) and to the clarification of theoretical debates concerning creative practices, by relating these subjects with the empirical data collected. Other factors related to creative capacity such as design education and knowledge and were also investigated. These analysis were possible through a bibliographical review and an exploratory qualitative research. Data was collected through semistructured interviews with Architecture and Urbanism students. The data was organized and the results were analysed, intending to broaden knowledge on the subject. A model open to discussion was created to promote reflections in future studies about the development of ideas in Architecture.